Current Developments in Catalytic Methanation of Carbon DioxideA Review - Tan C.H.; Nomanbhay S.; Shamsuddin A.H.; Park Y.-K.; Hernndez-Cocoletzi H.; Show P.L. (Frontiers Media S.A., 2023)
Atmospheric chemistry; Carbon capture; Catalyst activity; Catalyst selectivity; Fossil fuels; Global warming; Greenhouse gases; Hydrogenation; Methanation; Methane; Nickel; Precious metals; 'current; Anthropogenics; Atmospheric carbon dioxide; CO 2 emission; CO2 methanation; Gas technologies; Global warming and climate changes; Power; Severe weather; ]+ catalyst; Carbon dioxide